(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The difficulties encountered in translating Charles Perrault’s fairy tales into Uzbek are the main topic of this article. This article discusses the changes and misinterpretations of his tale by three translators.